اُردومیں فرہنگ نویسی کی روایت:ایک جائزہ - Yaqoob Khan ,; Dr. Salman Ali, (Khayaban - خیابان, 2021)
Abstract: A glossary is an alphabetical order of terms in a specific domain of Knowledge with the definitions and explanations of these terms.In recent times,two types of glossary are well known .the first is given at the end of a book and it contains difficult and uncommon. Terms within that books the second type of glossary is a book. In itself that includes a lot of difficult words alongwith their mean Ing with reference to their context